2023
DOI: 10.1089/can.2022.0046
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids, Anandamide and 2-Arachidonoylglycerol, as Prognostic Markers of Sepsis Outcome and Complications

Abstract: Background: One of the major challenges in improving sepsis care is early prediction of sepsis complications. The endocannabinoid system has been intensely studied in recent years; however, little is known about its role in sepsis in humans. This study aimed to assess the prognostic role of endocannabinoids, anandamide (AEA) and 2-arachidonoylglycerol (2-AG), as early predictors of mortality, invasive mechanical ventilation (IMV) requirement, and length of stay (LOS) in patients with sepsis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Recent research findings suggest that low baseline plasma AEA levels may serve as prognostic indicators for septic patients requiring prolonged mechanical ventilation. Furthermore, a lower concentration of AEA has been identified as a prognostic factor for hospital stays exceeding 10 days (30). In another study, AEA was found to attenuate acute respiratory distress syndrome induced by Staphylococcus Enterotoxin B by suppressing inflammation through the down-regulation of key miRNA that regulates immunosuppressive pathways (31).…”
Section: Discussionmentioning
confidence: 98%
“…Recent research findings suggest that low baseline plasma AEA levels may serve as prognostic indicators for septic patients requiring prolonged mechanical ventilation. Furthermore, a lower concentration of AEA has been identified as a prognostic factor for hospital stays exceeding 10 days (30). In another study, AEA was found to attenuate acute respiratory distress syndrome induced by Staphylococcus Enterotoxin B by suppressing inflammation through the down-regulation of key miRNA that regulates immunosuppressive pathways (31).…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, beyond the roles of CB 1 R and CB 2 R in immune and physiological regulation, researchers have explored the indicators of altered eCB production as potential markers for sepsis severity. A study encompassing 106 hospitalized sepsis patients showed that patients with diminished AEA and 2-AG levels necessitated extended hospital stays and invasive mechanical ventilation ( 159 ).…”
Section: The Impact Of Ecs and Cannabinoids On Bacterial Infectionsmentioning
confidence: 99%